The translation of onomatopoeias in comics: linguistic and pedagogical implications - Munoz-Luna, Rosa (Lingua Posnaniensis, 2019)
The present paper aims to compare and analyse three versions of Garfield comic strips, the original and two different translations into Spanish (from the United States, Spain and Argentina, respectively). More specifically this case study focuses on the treatment of onomatopoeias and interjections in the translations, with the purpose of examining the degree of influence of culture and context in the different linguistic equivalents. Finally, some pedagogical implications of the use of comic strips in the foreign language classroom are also discussed.